Sanctions and the Exchange Rate - Oleg Itskhoki; Dmitry Mukhin (Intereconomics, 2022)
Stabilising the exchange rate allows the Russian government to anchor inflation expectations and support consumption but comes at the cost of the financial repression of domestic savers.
Keywords: F51; F31; F41; 330